(untitled) (Singaporean Journal of Business Economics and Management, 2013)
The issues of media, gender, and conflict have long been a major area of research in media studies. These studies focus on the way women have been portrayed, and looked at as media. Practitioners vis-a-vis sex objects. This study provides a comprehensive overview of the continue stereotypes of women. This studies media stereotypes and the depiction of women in Nigeria media as well as the problems of gender bias.